THE IMPLEMENTATION OF TEACHING ENGLISH TO THE TENTH GRADE STUDENTS AT SMK NEGERI 8 SURAKARTA IN 2015/2016 ACADEMIC YEAR - Jannah, Syilvia Mustanuri (Universitas Muhammadiyah Surakarta, 2015)
The study is aimed at analyzing the implementation of teaching English at State Vocational High School 8 Surakarta in 2015/2016 academic year. The objectives of the study are to describe and explain the implementation of teaching English at this school. In this research, there are seven components of the implementation of teaching English which are investigated, namely: learning objective, syllabus, instructional material, classroom procedure, techniques in teaching English, media, and assessment. The type of the study is descriptive qualitative research especially naturalistic approach. The data are derived from event, informant, and document. There are three methods of collecting data, namely: observation, interview, and document. The process of analyzing data includes data reduction, data display, and conclusion or verification. The results of the study are as follows: (1) There are two learning objectives of teaching English namely: general objective and specific objective. The general learning objective is based on curriculum and specific learning objective is based on the syllabus; (2) The type of syllabus is mixed syllabus, consisting of structural syllabus, notional syllabus and functional syllabus; (3) The instructional material used is printed material; (4) The classroom procedure used is observing, questioning, experimenting, associating, and communicating; (5) Techniques used in teaching English are reading aloud, silent reading, questioning session, group work, brainstorming, reading comprehension, individual, discussion, role play, and exercise modeling; (6) The media used in teaching learning process is white board and picture and image; and (7) Assessment types used are final test preparation, daily assessment, mid test, and final test.